Peran Human Capital Business Partner & General Service PT Angkasa Pura 1 Kantor Cabang Adi Soemarmo Terhadap Efektivitas Kinerja Perusahaan - Intan Nurrohmah, Rahmadini; Retno Cahyani, Rusnandari (Universitas Sahid Surakarta, 2023)
The purpose of this article is to explain that human capital does not only reflect as